Prevention and Infection Control in Dental Practices During the Covid-19 Pandemic: A Literature Review - Ratri Ayu Shintya; Yuanita Windusari; Rizma Adlia Syakurah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2021)
Dental practices have a high risk of infected Covid-19 when providing dental and oral health services. The highest infections among all health care professions are dentists, dental assistants, and dental hygienists, because these professions are associated with patients and exposure to salivary secretions and aerosols. To be able to reduce the risk and the transmission of Covid-19 virus in dental practice, it is necessary to prevent and control infection during the Covid-19 pandemic. Therefore, the purpose of this study is to analyze infection control prevention in dental practices during the Covid-19 pandemic. This type of research is a literature review with a qualitative approach through descriptive analysis. The selection of articles according to the specified inclusion and exclusion criteria. The search process for this article was carried out using Google Scholar, Pubmed, DOAJ and Springerlink databases using the keywords